Interaction Effects of Human Resource Capacity and Policy Innovation on Local Tax Collection Effectiveness - Summeh, Fitri Sugianti; Suharto, Rahcmad Budi; Lestari, Diana (Research Horizon, 2026)
The effectiveness of local tax collection has become a critical issue in regional fiscal sustainability, particularly amid increasing policy innovation and administrative transformation. This study aims to examine the influence of human resource capacity and policy innovation on the effectiveness of local tax collection in Bontang City and to analyze the interaction between these variables. A quantitative associative approach was employed using time series data from 2015–2024, including tax targets, realization data, and personnel records from the Regional Revenue Agency (Bapenda) of Bontang City. Data were analyzed using multiple linear regression with dummy variables and interaction terms through SPSS software. The findings reveal that human resource capacity does not significantly affect tax collection effectiveness, while policy innovation serves as the primary driver with a significant positive impact, indicating a structural shift in regional fiscal capacity. Moreover, a significant negative interaction effect was identified, suggesting that increasing personnel during innovation implementation reduces effectiveness due to transitional inefficiencies and administrative coordination burdens. The study concludes that regional tax administration has shifted from a labor-intensive toward a system-intensive model, emphasizing the need for automated data integration rather than workforce expansion.